Optimalisasi Dakwah Melalui Radio, Analisis Program Kuliah Subuh Radio Gema Surya FM Ponorogo (RGS FM) - Predianto Predianto; Nurul Iman; Azid Syukroni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Learning knows no time and space. Every movement or action in order to achieve a certain goal, then it can be said to be learning. To achieve this goal, a person needs a device or media as a support in the process of obtaining the expected information. Radio is one of the information media that can be enjoyed by all listeners to achieve certain goals. Such a purpose is to learn about the religion of Islam. On this occasion, researchers have the aim of researching one of the radios in Ponorogo, precisely is the Gema Surya FM radio. Researchers want to research the implementation of Da'wah Optimization Through Radio (Analysis of the Subuh Lecture Program of Radio Gema Surya Fm Ponorogo (RGS fm). The objectives of this study are 1) To find out what the Fajr Lecture program at RGS FM Ponorogo is, 2) To find out how the Fajr Lecture program at RGS FM Ponorogo, 3) To find out the supporting and inhibiting factors in the production and broadcasting process of the Fajr Lecture program at RGS FM Ponorogo.The approach to this research is a qualitative approach, with a type of case study research. Data collection techniques through interviews, observation and documentation. Data analysis uses data reduction, data presentation and data inference.The results showed that the Fajr Lecture Program is a daily program that airs from 05.00 to 05.30 WIB. The program has a monologue da'wah program format. Da'wah material at the RGS FM Fajr Lecture was delivered by speakers who were competent in their fields, On Islamic holidays, Fajr Lecture broadcast selected material according to the situation that was happening. The supporting elements in the Fajr Lecture program are supported by advanced technological tools with a wider reach through internet streaming, which is an easy solution for the production process of the Fajr Lecture program. Until now, Kuliah Subuh is a program that is in demand by listeners because of its prime time so that this program continues to air. While the factors that hinder this program are resource persons. The resource person when unable to attend will change the format by using the lecture recording.